P183 Risk of eating disorders in italian children and adolescents with Inflammatory Bowel Disease: results of a multicenter nationwide study. (27th May 2021) - Gatti, S; Vallorani, M; Zoppi, E; Palego, G; Aloi, M; Bramuzzo, M; Felici, E; Zuin, G; Borali, E; Catassi, G; Grazian, F; Quagliarella, A; et al.
Abstract: Background: The prevalence and risk of Eating Disorders (ED) in IBD, despite the potential overlap of these two conditions, have been rarely reported. ED diagnosis should be considered in patients with IBD and multidisciplinary approach would be recommended in these complex cases to provide an adequate therapeutic intervention. Screening tools to evaluate eating attitudes and behaviours in patients with IBD could be used in daily practice, as for example the Eating Attitude Test – 26 Methods: Children and adolescents (8–18 years) with IBD and age and gender matched healthy controls were prospectively enrolled in 5 italian pediatric IBD units between June 2019 and August 2020. Subjects with an existing diagnosis of ED were excluded. The risk of ED was assessed using a 26 points Likert scale screening tool (CH-EAT-26 and EAT-26 for children < and > 14 years respectively), with a total score of 20 or above indicating a risk for ED. Correlations between clinical and disease's parameters and the CH-EAT-26/EAT-26 score were calculated Results: 110 patients with IBD and 110 age and matched healthy controls were screened with the CH-EAT26/EAT-26 questionnaire. The total EAT26 scores and the prevalence of an at-risk score (score>20) did not differ in IBD subjects compared to controls. IBD patients were more frequently on an exclusion diet with lactose free-diet being the most common regimen. Furthermore, 8.1% of IBD children was on a partial enteral nutrition (PEN). In IBD subjects elevated scores on the Ch-EAT26/EAT-26 were associated with being younger (r=-0, 2226, p=0.002), following an exclusion diet (r=0.25, p=0.009) and a partial enteral nutrition (PEN: r=0, 2507, p=0.009). Type, duration and activity of disease, gender, weight, height and BMI z-scores were not significantly correlated to the CHEAT26/EAT-26 score. Being on a PEN and following an exclusion diet were the only independents factors influencing the EAT26 score at the multiple regression analysis (p= 0, 004; p= 0, 034; R2 = 0, 25) Conclusion: Our results indicate that 5.45% of IBD children have a behavior at risk for developing an ED, a percentage that is not statistically different compared to healthy controls. A particular follow-up should be reserved to patients on restricted diets and on partial enteral nutrition, that can develop maladaptive attitudes toward eating. The development of a disease specific tool or a validation of pre-existing questionnaires would help to identify a robust screening instrument and ultimately to correctly classify the risk of patients. Once the risk is correctly assessed it is mandatory to address the patient to a specific multidisciplinary follow-up.